Augmented Reality Portal Using Markerless Method at the Ergendang Cave Tourist Attraction - Rahmadina, T Ahyuza; Sinaga, Tantri Hidayati; Nurjamiyah , Nurjamiyah (Jurnal Galaksi, 2024)
For some visitors, natural tourism represents an attractive form of tourism in itself. One of the most notable natural attractions in North Sumatra is Ergendang Cave, situated in Penungkiren, Sinembah Tanjung Muda (STM) Hilir, Deli Serdang Regency. The promotional media for Ergendang Cave still exhibits deficiencies that impede its ability to attract local tourists. The utilisation of augmented reality (AR) technology has the potential to enhance the efficacy of promotional media by facilitating the creation of portal applications that integrate the virtual and tangible realms through markerless methodologies. This Android-based application has been constructed using the Unity 3D platform and the C# (sharp) programming language, in accordance with the prototype model SDLC system development method. This study presents information on the surrounding situation of Ergendang Cave tourism with 360° panoramic photos through a portal that aims to help attract tourists. The portal provides users with the ability to virtually visit the location in real time, effectively bridging the gap between the user's physical location and the virtual representation of Goa Ergendang Tourist Attractions. This could be particularly beneficial during the ongoing pandemic, as it offers a unique opportunity for tourists to virtually experience the attractions without the need for physical travel.